2014
DOI: 10.1016/j.jmarsys.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Microorganism dynamics during a rising tide: Disentangling effects of resuspension and mixing with offshore waters above an intertidal mudflat

Abstract: Resuspension of microphytobenthic biomass that builds up during low tide has been acknowledged as a major driver of the highly productive food web of intertidal mudflats. Yet, little is known about the contribution to pelagic food web of the resuspension of other microorganisms such as viruses, picoeukaryotes, cyanobacteria, bacteria, nanoflagellates, and ciliates, living in biofilms associated with microphytobenthos and surficial sediment. In the present study, a novel approach that involves simultaneous Lagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…Waves and current BSS can also shape the spatial distribution of P. ulvae individuals on the mudflat (Armonies & Hartke, ) and so the local grazing pressure on MPB developing in the sediment. In the model, the lack of grazing pressure on MPB cells resuspended in the water column may result into an overestimation of the simulated resuspended MPB biomass (Guizien et al, ). The intensive oyster farming in the Brouage mudflat vicinity can result into a substantial removal of the resuspended MPB biomass (Smaal & Zurburg, ).…”
Section: Discussionmentioning
confidence: 99%
“…Waves and current BSS can also shape the spatial distribution of P. ulvae individuals on the mudflat (Armonies & Hartke, ) and so the local grazing pressure on MPB developing in the sediment. In the model, the lack of grazing pressure on MPB cells resuspended in the water column may result into an overestimation of the simulated resuspended MPB biomass (Guizien et al, ). The intensive oyster farming in the Brouage mudflat vicinity can result into a substantial removal of the resuspended MPB biomass (Smaal & Zurburg, ).…”
Section: Discussionmentioning
confidence: 99%
“…The input of freshwater into estuarine systems could reduce the efficacy of these bridges, releasing pathogenic bacteria such as V. cholerae from sediment into the water column (Kierek and Watnick, 2003). Guizien et al (2014) found that bacterial numbers decreased due to grazing and that viral titre in the water column did not significantly increase due to re-settlement of virus-clay complex, suggesting a complex story governing resuspension of enteric microorganisms. The risk associated with the sediment of enteric microorganisms depends on concentration, the ease with which bacteria resuspend or release back into the water column, and the frequency with which this will occur (Cox et al, 2005).…”
Section: Sediments As a Sink/source Of Fecal Bacteria And Viruses?mentioning
confidence: 99%
“…In the water column, the dynamics of benthic viruses may be globally governed by the trade-off between their irreversible and non-infective adsorption onto benthic-suspended matter (Suttle and Chen, 1992) and their multiplication at the expense of more active attached bacteria (Kernegger et al, 2009;Riemann and Grossart, 2008). The abundance of HNF depends directly on the resuspension of their benthic representatives and would also, in the case of muddy sediments, indirectly benefit from the increase of their prey (bacteria and pico-, nanoautotrophs), which benefit from the input of benthic nutrients (Garstecki et al, 2002;Guizien et al, 2013). Thus, the microbial interactions include HNF bacterivory, HNF virivory (Bettarel et al, 2005), viral lysis of bacteria, HNF or viruses and coincidental HNF predation of infected bacteria (Miki and Jacquet, 2008).…”
Section: Introductionmentioning
confidence: 99%